Maternal health service utilization in the Jimma Zone, Ethiopia: results from a baseline study for mobile phone messaging interventions - Gebeyehu Bulcha; Hordofa Gutema; Demisew Amenu; Zewdie Birhanu (BMC, 2024)
Abstract Background Over the last 20 years, global healthcare has placed a major focus on improving the survival rates of mothers and children, recognizing the potential to prevent a significant number of deaths resulting from pregnancy and childbirth. Nevertheless, there remains an ongoing obstacle to the insufficient utilization of critical obstetric services to achieve optimal health outcomes for pregnant women. This study aimed to assess the magnitude and determinants of maternal healthcare use in the Jimma Zone, Ethiopia. Methods Data were obtained from a household survey as part of the baseline assessment of a cluster randomized controlled trial. The study participants comprised 588 women in early pregnancy, specifically those with a gestational age of less than 20 weeks. Logistic regression analysis was employed to identify factors associated with the use of maternal health services. Adjusted odds ratios (AORs) were used to assess the strength of the associations, with significance level set at a p-value ≤ 0.05. Results The overall prevalence of maternal health service utilization was 87.9% (CI: 85.1, 90.4) for antenatal care, 74.7% (CI: 73.2, 79.9) for health facility delivery, and 60.4% (CI: 56.4, 64.3) for postnatal care. Multivariable logistic analysis revealed that maternal health service use was significantly influenced by access to health facilities (AOR: 6.6; 95% CI: 2.39, 18.16), financial hardship (AOR: 3; 95% CI: 1.97, 4.61), perceived respectful care (AOR: 2.3; 95% CI: 1.07, 5.11), perceived privacy of service provisions (AOR: 2.4; 95% CI: 1.47, 4.06), and attitudes toward maternal service use (AOR: 2.2; 95% CI: 1.48, 3.24). Conclusions The study revealed slightly higher rates of antenatal care, facility delivery, and postpartum care utilization. However, there was a low proportion of early antenatal care initiation, and high rates of antenatal care dropout. Mobile phone-based messaging intervention may enhance maternal health service use by addressing factors such as lack of access, economic challenges, disrespectful care, no privacy of procedures, and unfavorable attitudes.